The Impact of College Graduates on Bahamian Society: With Emphasis on Graduates from The College of The Bahamas - Fielding, William J. (International Journal of Bahamian Studies, 2015)
Society at large, both government and residents, invests in education, a process which is considered to reach its apex with a university qualification. Economically, education is typically seen to be both a private and public good, and so it is useful to determine the benefits to both the individual and society arising from this investment. This paper examines the economic contributions of university-educated Bahamians to society. Using information obtained from The College of The Bahamas and other official sources, the study demonstrates that having a populace with higher education has a beneficial impact upon the Bahamian economy.